2013
DOI: 10.1186/2162-3619-2-10
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of miR-221 is associated with shorter overall survival in T-cell acute lymphoid leukemia

Abstract: BackgroundCD56 expression has been associated with a poor prognosis in lymphoid neoplasms, including T-cell acute lymphoblastic leukemia (T-ALL). MicroRNAs (miRNAs) play an important role in lymphoid differentiation, and aberrant miRNA expression has been associated with treatment outcome in lymphoid malignancies. Here, we evaluated miRNA expression profiles in normal thymocytes, mature T-cells, and T-ALL samples with and without CD56 expression and correlated microRNA expression with treatment outcome.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 30 publications
0
48
0
1
Order By: Relevance
“…Aberrant expression of miRs has been well described in human GC (Pan et al, 2013). Specifically, miR-221 has been confirmed to be upregulated and may act as an oncogene in many types of human malignancies (Gimenes-Teixeira et al, 2013;Sarkar et al, 2013;Ergun et al, 2014;Sun et al, 2014;Ye et al, 2014a). Liu et al (2012) reported that upregulation of miR-221 in GC correlated with aggressive clinicopathological features and shorter overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant expression of miRs has been well described in human GC (Pan et al, 2013). Specifically, miR-221 has been confirmed to be upregulated and may act as an oncogene in many types of human malignancies (Gimenes-Teixeira et al, 2013;Sarkar et al, 2013;Ergun et al, 2014;Sun et al, 2014;Ye et al, 2014a). Liu et al (2012) reported that upregulation of miR-221 in GC correlated with aggressive clinicopathological features and shorter overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, miR-221 was identified as the most significantly modulated miRNA in the two PCa GEO datasets. MiR-221 is de-regulated in variety of cancers, primarily as an over-expressed miRNA [55][59].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have focused on the prognostic impact of epigenetic changes in pediatric T‐ALL, reporting, for example, that high levels of miR‐16 and miR‐221 are associated with shorter survival. This has, however, not been seen in all studies and, furthermore, these studies were based on quite a low number of patients, which often included both pediatric and adult patients, precluding any firm conclusions as to the prognostic role of miRs in childhood T‐ALL (Kaddar et al, ; Gimenes‐Teixeira et al, ; Xi et al, ). Data on promoters that are differentially methylated in T‐ALL have been applied to define CpG island methylator phenotypes, delineating cases as either hypermethylated or hypomethylated (Borssén et al, ), with hypomethylated cases having a significantly worse event‐free and overall survival in one of the studies (Borssén et al, ).…”
Section: Clinical Genetic and Epigenetic Features And Prognosismentioning
confidence: 99%